History and progress of antiviral drugs: from acyclovir to direct-acting antiviral agents (DAAs) for Hepatitis C - Bryan Marrugo, Owen Lloyd; Ramos Jiménez, Javier; Barrera Saldaña, Hugo Alberto; Rojas Martínez, Augusto; Vidaltamayo, Román; Rivas Estilla, Ana María (UANL. Facultad de Medicina, 2015)
The development of antiviral drugs is a very complex process. Currently, around 50 drugs have been approved for human use against viruses such as HSV, HIV-1, the cytomegalo virus, the influenza virus, HBV and HCV. Advancements in this area have been achieved through efforts and technical breakthroughs in different scientific fields. The improvement in the treatment of HCV infection is a good example of what is needed for efficient antiviral therapy. A thorough description of the events that lead to the development of specifically targeted antiviral therapy or HCV (STAT-C) could be useful to further improve research for treating many other viral diseases in the future. Similar to HIV-1 and HBV treatment, combination therapy along with personalized medicine approaches have been necessary to successfully treat HCV patients. This review is focused on what has been done to develop a successful HCV therapy and the drawbacks along the way